How does a hidden curriculum operate: a case study of routine practices and rules in a fourth-grade classroom - Şahin, Sebahat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
The purpose of this study was to examine in detail how the hidden curriculum in a public primary school classroom operated through the routine practices and rules that characterize daily classroom experiences. The study sample consisted of the thirty-‐three fourth-‐grade students and the class teacher of a primary school located in a small town in Western Turkey, Eastern Marmara region. Students were from a low socio-‐economic background, nine of whom were Roma. The method of this study was qualitative, namely a case study. A fourth-‐ grade classroom was observed through a two-‐and-‐a-‐half-‐month period and interviews with the teacher and students were conducted. Observational and interview data about the routine implementations and rules characterizing the classroom experience were analyzed by using the descriptive analysis and content analysis methods. Findings revealed that students remained passive during daily routine activities in classroom. They were limited to the activities within the frame determined by the teacher. Furthermore, it was observed and stated by the students that the teachers acted anti-‐democratically during determining and implementing the classroom rules. Students’ perceptions of the rules about were formed through the teacher approval. The teachers gave more importance to the continuity of classroom functioning -‐organization than to the social and cognitive development of the students, and recognized the negative behaviors of students more frequently than the positive ones. Finally, it was observed that the students from different ethnic origins were in more disadvantageous position and excluded when compared students from dominant cultural background.
Keywords: Curriculum planning -- Turkey.; Education -- Curricula -- Turkey.